Crystal structure of new barium manganese fluorides dihydrates, Ba10Mn2F25·2H2O - Kim Sun Woo; Chang Hong Young (Zeitschrift für Kristallographie - New Crystal Structures)
Ba10Mn2F25·2H2O, cubic, Fd3̄m (no. 227), a = 17.487(2) Å, V = 5347.7(18) Å3, Z = 8, Rgt (F) = 0.0236, wRref (F 2) = 0.0552, T = 296(2) K.